2015
DOI: 10.1371/journal.pone.0127866
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Recommended by the World Health Organization: DNA Barcode Identification Associated with Chemical Analyses Guarantees Their Quality

Abstract: Medicinal plants are used throughout the world, and the regulations defining their proper use, such as identification of the correct species and verification of the presence, purity and concentration of the required chemical compounds, are widely recognized. Herbal medicines are made from vegetal drugs, the processed products of medicinal species. These processed materials present a number of challenges in terms of botanical identification, and according to the World Health Organization (WHO), the use of incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 54 publications
2
109
0
6
Order By: Relevance
“…As this study considered fillers, the level of adulteration was inflated in comparison with other studies that did not consider fillers such as wheat and rice. Other studies of adulteration in NHPs have found similar estimates, including a recent paper, which revealed that the level of substitutions may be as high as 71% [102]. Supportive research has documented adulteration many herbal products including 50 % in ginseng and 25 % in black cohosh [71,75], 33 % in herbal teas [76] and 16 % in Ginkgo products [69].…”
Section: Sanger Dna Sequencingmentioning
confidence: 65%
See 1 more Smart Citation
“…As this study considered fillers, the level of adulteration was inflated in comparison with other studies that did not consider fillers such as wheat and rice. Other studies of adulteration in NHPs have found similar estimates, including a recent paper, which revealed that the level of substitutions may be as high as 71% [102]. Supportive research has documented adulteration many herbal products including 50 % in ginseng and 25 % in black cohosh [71,75], 33 % in herbal teas [76] and 16 % in Ginkgo products [69].…”
Section: Sanger Dna Sequencingmentioning
confidence: 65%
“…DNA barcoding is not considered to be inappropriate by the FDA, but it currently does not yet use DNA barcoding for authentication of botanical extracts [101]. According to the World Health Organization (WHO), the use of incorrect species is a threat to consumer safety and a recent large study [102] of NHP adulteration has concluded that DNA barcoding should be used in a complementary manner for species identification alongside chemical analyses to detect and quantify the required chemical compounds, thus improving the quality of NHPs. In Europe, the European Medicines Agency (EMA) has issued numerous guidelines concerning the quality and testing of herbal substances and herbal medicinal products [7].…”
Section: Barcoding and Pharmacovigilance Of Herbal Medicinementioning
confidence: 99%
“…This effort was made for proper identification of safe plants, as it is estimated that plant-based traditional medicines are used by 60% of the world's population [90]. In addition to efforts to establish formal, DNA-based identification of such plants for wider use [91], collections of medicinal plant species, and in particular of phytochemicals, NPs produced by plants, associated to their therapeutic activities and physicochemical properties are being established around the world. This is particularly the case in Asia and Africa, where traditional medicines remain an important part of everyday life for cultural, traditional and economic reasons.…”
Section: Natural Products By Usementioning
confidence: 99%
“…pendimethaline) [48,49]. High requirements concerning the purity of plant-derived materials allow us to maintain the content of bioactive substances on a desired high level that would be sufficient to produce therapeutic effects in patients who take the plant-derived medicines [50][51][52][53]. At present, to collect plant raw materials, we are obliged to cultivate the respective medicinal herbs and plants.…”
Section: State-of-the-art Knowledgementioning
confidence: 99%